‘Barbaro è di costume, empio di fede’? Sul nativo americano nell’epica del Seicento - Artico, Tancredi (Incontri. Rivista europea di studi italiani, 2017)
‘Barbaro è di costume, empio di fede’? About the Native American in seventeenth-Century EpicThe purpose of this article is to investigate the representation of Native Americans in seventeenth-century Italian epic by identifying two opposite ethical-literary approaches and connecting them to modern literary theories on epic and imperialism. The first poem I examine, Tommaso Stigliani’s Mondo Nuovo, unites the ideology of Homer’s Iliad and of the Spanish Empire and gives a negative idea of the native, seen as a brute and unholy follower of Satan. The second poem, Girolamo Bartolomei’s America, is based on the scheme of the Odyssey and recalls the philanthropic theories of Bartolomé de Las Casas by emphasizing the original purity of Native Americans and describing its corruption through the brutality of the conquerors. This examination of the representation of the native thus argues that the ethical and political implications of the prevailing model in early modern epic, the Iliad, were countered by a (nowadays neglected) archetype, the Odyssey.